Atmospheric-Pressure Plasma Jet Processed Carbon-Based Electrochemical Sensor Integrated with a 3D-Printed Microfluidic Channel. Issue 12 (17th August 2017) - Yang, Cheng-Han; Chen, Chieh-Wen; Lin, Yu-Kuan; Yeh, Yi-Chun; Hsu, Cheng-Che; Fan, Yu-Jui; Yu, Ing-Song; Chen, Jian-Zhang
Abstract : This paper reports prototype atmospheric-pressure plasma jet (APPJ)-processed reduced graphene oxide (rGO)-modified carbon electrochemical sensors integrated with 3D-printed microfluidic channels. Dopamine (DA) solutions with various concentrations are used for the model test. The APPJ-calcined rGO coating significantly enhances the electrochemical signal for DA detection by 18 times. X-ray photoelectron spectroscopy (XPS) shows that APPJ-calcined rGO-modified carbon electrodes have more oxygen-containing surface functional groups, leading to the enhanced electrochemical reactivity. The cyclic voltammetry (CV) curves of solutions with various DA concentrations are well-distinguishable in the presence of uric acid (UA) and ascorbic acid (AA) as interfering agents.